Selection of low impact development technical measures in the distribution area of expansive soil: a case study of Hefei, China - Huang, Ming; Liu, Zhen; Zhang, Rui; Tao, Yong; Sun, Ya-min (Frontiers in Environmental Science, 2024)
Expansive soils are widely distributed around the world. Their characteristics of both water-absorbing expansion and water-losing contraction have caused serious damage to road paving, construction of low-rise houses, and construction of slopes along the banks of rivers. Similarly, the implementation of low-impact development measures can cause considerable difficulties in the distribution area of expansive soil. The entire urban area of Hefei is situated in top of the expansive soil. Although Hefei City has developed a sponge city plan, it has not been carried out on a large scale to implement low-impact development technical measures. Experimental studies have shown that exposed expansive soils produce fissures that run up and down during wet and dry cycles. These fissures are extremely unfavorable to the infiltration of surface runoff formed by short-term heavy rainfall. This is also one of the reasons why Hefei City suffered a short calendar period of heavy rainfall resulting in serious flooding in low-lying poor drainage areas. At the same time, initial rainfall is ineffective in cleaning up surface source pollution. Therefore, we can improve the characteristics of expansive soil, keep the expansive soil not exposed and have a certain humidity. These approaches can play a better role in the control of rainfall runoff and surface source pollution. Expansive soils can be improved by mixing with weathered sand, a physical improvement, to meet the technical requirements for infiltration and interception and purification. It is recommended to carefully select low-impact development measures in the distribution area of expansive soil, to avoid the occurrence of wasteful investment and poor results.